ANALISIS STRATEGI BERSAING PADA PERUSAHAAN LUXIOR DI BANDUNG - Fransisca Lili Koswara (Jurnal Administrasi Bisnis, 2019)
This research was conducted to analyze the competitive strategy applied by the companies to compete appropriately. In addition, this study was also conducted to find out the description and competitive strategies carried out by companies, especially companies engaged in interior design and furniture field. The researcher took samples from the Luxior Company, Bandung. This research used interview and observastion as a data collecting method. The interview was conducted with the Luxior company which aims to find out the right competitive strategy. This study uses five force model analysis, value chain analysis, and SWOT matrix analysis to find out information and environmental conditions both internally and externally. Based on the results of the study, Luxior Company used best cost provider strategy. This strategy has meaning of more value for the money, which means that consumers are willing to pay more because they want more value and benefits.